Lesser tuberosity is more reliable than bicipital groove when determining orientation of humeral head in primary shoulder arthroplasty - Hromádka, Rastislav; Kuběna, Aleš; Pokorný, David; Popelka, Stanislav; Jahoda, David; Sosna, Antonín (Surgical and radiologic anatomy, 2010)
PURPOSE: The objective of the study was to provide statistical evaluation of position of bone landmarks of proximal humerus in relation to transepicondylar line and find out which one is the most suitable for setup of the head retroversion in case of humeral head destruction. METHODS: We measured 185 dry humeral preparations (92 left, 93 right). Structures of interest on the proximal humerus were marked with pointers of custom made steel frame. Angular relationships between the humeral head axis and medial margin of the greater tuberosity, lateral margin of the lesser tuberosity, bicipital groove, and crest of the greater tuberosity were evaluated with respect to intramedullary axis of the proximal humeral shaft. RESULTS: The angle between the humeral head axis and medial margin of greater tuberosity was 11.5 +/- 9.0 degrees , the angle between the lateral margin of the lesser tuberosity and the axis was 47.5 +/- 7.4 degrees , the angle between the bicipital groove and the axis was 31.6 +/- 8.8 degrees at the level of the humeral head. The angle between the crest of the greater tuberosity and the axis was 26.6 +/- 9.6 degrees in plane of the surgical neck. CONCLUSIONS: We statistically proved that the lateral margin of lesser tuberosity is more reliable than the bicipital groove; medial margin of the greater and transepicondylar line for reconstruction of humeral head retroversion. We suggest that the lesser tuberosity should be used to determine the retroversion, especially in cases when the margin of humeral head was destructed.
Keywords: Arthroplasty; Humans; artroplastika; ramenní kloub; humerus; Shoulder Joint; lidé; Humerus